Assessment of progress in the implementation of the Programme of Action for LDCs for the decade 2001-2010 : UNCTAD's contribution to the mid-term review : progress made, results achieved and lessons learned (UN New YorkUS, 2006)
Provides an overview and synthesis of the country case studies and national reports. Presents policies, conclusions and recommendations aimed at assisting the further implementation of actions and commitments of the PoA at the national and international levles.
Keywords: ECONOMIC AND SOCIAL DEVELOPMENT